Onset of a submarine eruption east of Mayotte, Comoros archipelago: the first ten months seismicity of the seismo-volcanic sequence (2018–2019) - Mercury, Nicolas; Lemoine, Anne; Doubre, Cécile; Bertil, Didier; Van Der Woerd, Jérôme; Hoste-Colomer, Roser; Battaglia, Jean (Comptes Rendus. Géoscience)
From 10 May 2018 to 1 November 2022 (time of writing), an unprecedented seismic activity is observed east of Mayotte Island (France), related to the largest submarine eruption ever recorded with offshore geophysical studies. Using signals from regional and local seismic stations, we build a comprehensive catalog of the local seismicity for the first ten months of the sequence. This catalog includes a total of 2874 events of magnitude (Mlv) ranging from 2.4 to 6.0, with 77% of them relocated using a double difference location procedure. The hypocentral locations over this period are highly dependent on the small seismic network available. Therefore we compare the locations of later events using a similar network and those estimated from a local ocean bottom seismometer (OBS) network installed since March 2019. Based on the time space evolution and characteristics of the seismicity, five distinct phases can be identified, corresponding to the successive activation of two deep seismic swarms, related to the lithospheric-scale magma ascent up to the seafloor, along with progressive deepening of the seismicity interpreted as decompression of a 40 km deep reservoir.